The Impact of Information Technology on Cyber Resilience - Ummu Ammelia; Vanessa Puspitasari; Suparmi (Annujum: Journal of Humaniora and Law, 2025)
Developments in information technology have a significant impact on a country cyber resilience. Information technology not only increases the effectiveness of communication and information access, but also strengthens the ability to detect and respond to digital threats through the use of artificial intelligence, big data, and multi-layered security systems. However, technological advances also pose risks such as the spread of hoaxes, data theft, and the increasing frequency of cyberattacks, which can threaten political, economic, and social stability. This study uses a descriptive qualitative approach through a literature review of various relevant sources to analyze the impact of information technology on Indonesia's cyber resilience. The result indicate that increasing digital literacy, updating cybercrime regulations, and strengthening security infrastructure are important factors in creating optimal cyber resilience. Collaborative efforts between the government, the public, and the private sector are needed to leverage information technology as a strategic opportunity, rather than a threat, to national security and resilience.